Carbon Emissions Caps and the Impact of a Radical Change in Nuclear Electricity Costs - Leibowicz, Benjamin D.; Roumpani, Maria; Larsen, Peter H. (International Journal of Energy Economics and Policy, 2012)
In this study we analyze the impact of a radical change in nuclear electricity costs on the optimal electricity generation technology mix (EGTM) and constrain the value of information (VOI) on future nuclear costs. We consider three nuclear cost events and four carbon emissions caps. We develop a two-stage framework for energy-economic model MARKAL to eliminate foresight of future nuclear cost movements. We examine how the EGTM responds to these movements under alternative caps and analyze how these movements affect the cost of each cap. We define the expected savings from perfect foresight (ESPF), an upper bound on the VOI. We found that with current technologies, carbon mitigation that does not rely heavily on nuclear electricity is economically insensible. The Strong Cap is extremely costly because it restricts flexibility to respond to cost signals in choosing among technologies. The ESPF is highest under the Medium Cap by a substantial margin. Keywords: MARKAL; nuclear electricity; value of information; foresight JEL Classifications: C60; H23; O13; O33; Q40; Q50